Influência da umidade na Avaliação Visual da Estrutura do Solo (VESS) - Cavalli, Aline (2020)
The soil has several physical, chemical and biological attributes that can define itsproduction. The structure of the soil is widely used as an indicator of soil quality, dueto its influence on the movement of water, and on roots in the soil profile. Severalmethods are used to study soil structure, including direct imaging methods such asX-ray tomography and electron microscopy. However, such methods are expensive,time-consuming and require training to be applied, in addition to having lowrepeatability and not being applied on-farm. The Visual Evaluation of Soil Structure,VESS, method has as its advantages speed of execution, on-farm execution and lowoperational cost. However, when carrying out the methodology on Brazilian soils ofbasaltic origin, which have high levels of clay and plasticity, the sampling effort andthe difficulty related to the execution of the methodology demands a betterknowledge of the favourable humidity conditions for the application of themethodology, specifically the appropriate moisture range for the evaluation. Thiswork consisted of quantifying the VESS structural quality (Sq) score in a typicaldystrophic oxisol over a wide range of established soil moisture levels. Thus, after a60 mm rain event, four evaluations were carried out every 24 hours in ahomogeneous area using the VESS methodology. The samples were collected fromthe experimental area of the Federal Technological University of Paraná, in PatoBranco, in the state of Paraná. Eleven different moisture levels were obtained, onefor each collection day. The results indicated that soil moisture interferes with theVESS score, especially in layers with a Sq score of 4. It was concluded that the bestmoisture condition occurred on the fifth day after soil saturation, which is equivalentto a matric potential range of between -150 to -250 hPa, corresponding to watercontents of between 0.447 and 0.430 m3m-3.